2015
DOI: 10.5662/wjm.v5.i2.68
|View full text |Cite
|
Sign up to set email alerts
|

Accurate diagnosis of myalgic encephalomyelitis and chronic fatigue syndrome based upon objective test methods for characteristic symptoms

Abstract: Although myalgic encephalomyelitis (ME) and chronic fatigue syndrome (CFS) are considered to be synonymous, the definitional criteria for ME and CFS define two distinct, partially overlapping, clinical entities. ME, whether defined by the original criteria or by the recently proposed criteria, is not equivalent to CFS, let alone a severe variant of incapacitating chronic fatigue. Distinctive features of ME are: muscle weakness and easy muscle fatigability, cognitive impairment, circulatory deficits, a marked v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 240 publications
1
22
0
Order By: Relevance
“…Considering the controversy with regard to the etiology and psychophysiology of ME and CFS [ 29 , 39 ] and the abstract and subjective nature of typical symptoms of ME and CFS, a diagnosis based upon self-reported measures is not adequate. As far is possible, objective methods should be employed to assess the symptoms and disability [ 35 ]. Characteristic symptoms, e.g., “fatigue,” long-lasting post-exertional weakness, cognitive impairment, post-exertional malaise (the negative effect of exercise on cognitive and physical performance levels) and visual problems can be “objectified” by using well-accepted methods, e.g., (repeated) cardiopulmonary exercise tests, neuropsychological tests (before and after an exercise test), (repeated) muscle power strength and endurance tests, tilt-table tests, and visual field tests.…”
Section: Proposal For a Methodological Solution For The Current “Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the controversy with regard to the etiology and psychophysiology of ME and CFS [ 29 , 39 ] and the abstract and subjective nature of typical symptoms of ME and CFS, a diagnosis based upon self-reported measures is not adequate. As far is possible, objective methods should be employed to assess the symptoms and disability [ 35 ]. Characteristic symptoms, e.g., “fatigue,” long-lasting post-exertional weakness, cognitive impairment, post-exertional malaise (the negative effect of exercise on cognitive and physical performance levels) and visual problems can be “objectified” by using well-accepted methods, e.g., (repeated) cardiopulmonary exercise tests, neuropsychological tests (before and after an exercise test), (repeated) muscle power strength and endurance tests, tilt-table tests, and visual field tests.…”
Section: Proposal For a Methodological Solution For The Current “Dmentioning
confidence: 99%
“…As the IOM report [ 14 ] states: “(Twisk) asserts that (…) objective assessment must address the unique symptoms in accordance with the diagnosis, whether it be ME or CFS” [ 34 ]. Various symptoms of ME and CFS can be assessed objectively, e.g., cognitive impairment, (post-exertional) muscle weakness, post-exertional “malaise” (long-lasting negative impact of exertion on symptoms) and orthostatic intolerance [ 35 ].…”
Section: Diagnostic Shortcomings Of the New Definition For “Me/cfsmentioning
confidence: 99%
“…This results in missed diagnoses and misdiagnoses, as illustrated by a study of Jason et al [23], which observed that a substantial subgroup of patients with other medical diseases, such as MS, lupus, and major depressive disorders, also qualify as being SEID [3] patients. For that reason, and because ME [1], CFS [2], and SEID [3] are considered to be controversial disorders, characteristic symptoms of ME [1], CFS [2], and SEID [3] should be assessed objectively [25], both in research projects as well as in clinical practice.…”
Section: Diagnosismentioning
confidence: 99%
“…The existence and magnitude of various characteristic symptoms of ME [2,3,4] and CFS [5] can be assessed objectively [41,42]. For example, loss of muscle power and prolonged muscle weakness after physical exertion [43] can be established by measuring muscle power during repeated contractions using dynamometers with 24 h rest in-between.…”
Section: Due To the New Definition Of “Me/cfs” The Four Recommendamentioning
confidence: 99%